Low Reproductivity of Giant Pandas May Be Associated with Increased Vaginal Escherichia-Shigella - Wei Wu; Fei Xue; Chong Huang; Yanshan Zhou; Guanwei Lan; Wenlei Bi; Jiabin Liu; Xiang Yu; Zusheng Li; Long Zhang; Feifei Feng; Jiang Gu; et al. (Microorganisms, 2024)
The poor reproductive capacity of giant pandas significantly hinders the development of captive populations, with 80.88% of adult individuals being unable to successfully become pregnant and deliver offspring. The disturbance of vaginal microbiota has been proven to potentially lead to miscarriage, abortion, and stillbirth in mammals. To elucidate the potential relationship between the vaginal microbiota and the reproductive capacity of giant pandas, we performed high-throughput sequencing of vaginal microbiota at the time of fertilization and conducted comparative analyses based on different pregnancy outcomes. We found that the microbial diversity in the delivery (D) group exceeded that in the non-delivery (ND) group and the vaginal microbial community structure was statistically different between the two groups. The vaginal microbiota in the delivery pandas consisted of unclassified Pseudomonadaceae which was gradually replaced by the Escherichia-Shigella type of vaginal microbiota in the ND group. A function predictions analysis showed that infectious disease, glycan biosynthesis, and metabolism were significantly enriched in the ND group. Additionally, an analysis of the microbial community phenotypic categories indicated that the ND group exhibited a significantly higher abundance of Gram-negative bacteria, facultative anaerobes, potential pathogens, and stress-tolerant species compared to the D group, predominantly driven by the elevated abundance of Escherichia-Shigella. Escherichia-Shigella can be used within LDA and ROC analyses to diagnostically distinguish the vaginal microflora associated with bad pregnancy outcomes during estrus. Our results will help to identify potential pathogens causing reproductive tract diseases, reduce the number of reproductive tract disease infections in pandas, and increase the birth rate of giant pandas in conservation breeding programs.